2012
DOI: 10.1210/jc.2011-2649
|View full text |Cite
|
Sign up to set email alerts
|

Link between Adipose Tissue Angiogenesis and Fat Accumulation in Severely Obese Subjects

Abstract: Angiogenesis may influence WAT expansion and plasticity but does not appear to be involved in the development of insulin resistance in subjects with severe obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 20 publications
0
30
1
Order By: Relevance
“…Chronic overfeeding leads to AT expansion due to adipocyte hypertrophy and is accompanied by enhanced vascularization to assure adequate oxygen supply which requires substantial ECM remodeling (Lemoine et al, 2012). In our model, deletion of Postn resulted in a reduced ability for AT expansion during HFD feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic overfeeding leads to AT expansion due to adipocyte hypertrophy and is accompanied by enhanced vascularization to assure adequate oxygen supply which requires substantial ECM remodeling (Lemoine et al, 2012). In our model, deletion of Postn resulted in a reduced ability for AT expansion during HFD feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is evidence for a functional link between adipogenesis and angiogenesis during deposition of fat mass, whereby the angiogenic capacity of WAT may determine the extent of adipogenesis and propensity of a subject to gain weight (37,38). In addition, several studies have shown that endothelial cells control adipogenesis in WAT through VEGF and matrix metalloproteinases pathways (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that adipose tissue in severely obese patients produces proangiogenic factors, including vascular endothelial growth factor (VEGF) and placental growth factor and, in these patients, BMI correlated with vascular density in subcutaneous white adipose tissue. However, after effective weight-lowering treatment, these abnormalities are reversed 14. Taken together, these data suggest that obesity has the potentiality to initiate many of the known immune-inflammatory pathways underlying the pathogenesis of PsA.…”
mentioning
confidence: 87%